BINATIONAL DIALOGUES ON THE CHALLENGES TO DOCUMENT THE (S) VIOLENCE (S) AGAINST INDIGENOUS WOMEN IN MEXICO AND CANADA - Jimenez-Estrada, Vivian; Don Juan Pérez, Norma; Torres Sandoval , Patricia; Figueroa Romero, Dolores (Universidade de Brasília, 2020)
This article is based on a dialogue that inquiries about the production of knowledge on gender violence that affects Indigenous women from Abya Yala and Tortuga Island. Here we critically analyze that institutional policies for the eradication of violence have not incorporated the analysis of the effects of colonial and structural violence that affects Indigenous women and their peoples. It is important to reverse this omission through documentation proposals from an intersectional and reflective perspective of the contexts. We believe that it will not be possible to respond to the demands for gender justice - both in the South and in the North - if we do not challenge the racism and coloniality that mediate the relationship between the State and Indigenous peoples, and that constitutes the experience of violence against Indigenous men and women.